The receptor-type protein tyrosine phosphatase CD45 promotes onset and severity of IL-1β-mediated autoinflammatory osteomyelitis - Kralova, Jarmila; Pavliuchenko, Nataliia; Fabisik, Matej; Ilievova, Kristyna; Spoutil, Frantisek; Prochazka, Jan; Pokorna, Jana; Sedlacek, Radislav; Brdicka, Tomas (The Journal of biological chemistry, 2021)
A number of human autoinflammatory diseases manifest with severe inflammatory bone destruction. Mouse models of these diseases represent valuable tools that help us to understand molecular mechanisms triggering this bone autoinflammation. The Pstpip2cmo mouse strain is among the best characterized of these; it harbors a mutation resulting in the loss of adaptor protein PSTPIP2 and development of autoinflammatory osteomyelitis. In Pstpip2cmo mice, overproduction of interleukin-1β (IL-1β) and reactive oxygen species by neutrophil granulocytes leads to spontaneous inflammation of the bones and surrounding soft tissues. However, the upstream signaling events leading to this overproduction are poorly characterized. Here, we show that Pstpip2cmo mice deficient in major regulator of Src-family kinases (SFKs) receptor-type protein tyrosine phosphatase CD45 display delayed onset and lower severity of the disease, while the development of autoinflammation is not affected by deficiencies in Toll-like receptor signaling. Our data also show deregulation of pro-IL-1β production by Pstpip2cmo neutrophils that are attenuated by CD45 deficiency. These data suggest a role for SFKs in autoinflammation. Together with previously published work on the involvement of protein tyrosine kinase spleen tyrosine kinase, they point to the role of receptors containing immunoreceptor tyrosine-based activation motifs, which after phosphorylation by SFKs recruit spleen tyrosine kinase for further signal propagation. We propose that this class of receptors triggers the events resulting in increased pro-IL-1β synthesis and disease initiation and/or progression.
Keywords: Animals; Adaptor Proteins, Signal Transducing; Osteomyelitis; Mice, Knockout; myši knockoutované; adaptorové proteiny signální transdukční; cytoskeletální proteiny; osteomyelitida; Mice; signální transdukce; myši; stupeň závažnosti nemoci; Signal Transduction; Diabetes Mellitus, Type 1; Cytoskeletal Proteins; Interleukin-1beta; Neutrophils; Leukocyte Common Antigens; neutrofily; interleukin-1beta; Toll-Like Receptors; zvířata; Severity of Illness Index; toll-like receptory; diabetes mellitus 1. typu; antigeny CD45